Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/jcmm.13501
|View full text |Cite
|
Sign up to set email alerts
|

Elevated mitochondrial activity distinguishes fibrogenic hepatic stellate cells and sensitizes for selective inhibition by mitotropic doxorubicin

Abstract: Activation of hepatic stellate cells (HSCs) is an integral component of the wound‐healing process in liver injury/inflammation. However, uncontrolled activation of HSCs leads to constant secretion of collagen‐rich extracellular matrix (ECM) proteins, resulting in liver fibrosis. The enhanced ECM synthesis/secretion demands an uninterrupted supply of intracellular energy; however, there is a paucity of data on the bioenergetics, particularly the mitochondrial (mito) metabolism of fibrogenic HSCs. Here, using hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…In addition, glutamine supports the respiration of activated HSCs [107]. Indeed, HSC activation leads to enhanced oxidative phosphorylation (OXPHOS) [108], a general feature of cells undergoing activation [109]. Inhibition of the Hh pathway with forskolin significantly reduced fibrosis development, oxidative stress, and inflammation in CCl 4 -treated rats [110].…”
Section: Central Carbon and Nitrogen Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, glutamine supports the respiration of activated HSCs [107]. Indeed, HSC activation leads to enhanced oxidative phosphorylation (OXPHOS) [108], a general feature of cells undergoing activation [109]. Inhibition of the Hh pathway with forskolin significantly reduced fibrosis development, oxidative stress, and inflammation in CCl 4 -treated rats [110].…”
Section: Central Carbon and Nitrogen Metabolismmentioning
confidence: 99%
“…As mentioned above, activated HSCs exhibit enhanced OXPHOS phenotype [108], which is typically associated with increased production of ROS in mitochondria [109]. Unfortunately, there is no data showing how enhanced ROS production from various sources (at various sites within HSCs) triggers cell activation and trans-differentiation into myofibroblasts.…”
Section: Redox Biologymentioning
confidence: 99%
“…Mitochondrial oxygen consumption rates were measured in an XF96 Extracellular Flux Analyzer (Seahorse Bioscience) as described previously described (10,34). Briefly, cells were plated at a density of 5,000 cells/well in an XF 96-well culture microplate and incubated for 24 h. To record oxygen consumption rates, the culture medium was replaced with Seahorse XF base medium supplemented with 25 mM glucose, 1 mM sodium pyruvate, and 2 mM GlutaMAX-I, and then the cells were incubated at 37°C in a CO 2 -free incubator for 1 h. Oxygen consumption rate analysis was initiated with a 13.5-min equilibration step, followed by three cycles of 2 min of mixing and 3 min of measurement.…”
Section: Mitochondrial Respirationmentioning
confidence: 99%
“…However, actual glycolytic rat and/or mitochondrial respiration were not quantified. Interestingly, others have shown that plastic-cultured r-aHSCs and LX-2 cells have higher mitochondrial and glycolytic metabolism compared to matrigel-cultured r-aHSCs and LX-2 cells [ 9 ]. Here, we show that the glycolytic rate is increased approximately 3-fold in culture-activated rHSCs versus freshly isolated r-qHSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhibiting these metabolic pathways has been shown to prevent the undergoing activation in vitro [ 7 , 8 ]. It has been recently demonstrated that plastic-cultured aHSCs have enhanced oxidative phosphorylation and glycolysis compared to less activated matrigel-cultured aHSCs [ 9 ]. However, functional analyses to quantify metabolic processes that differentiate freshly isolated qHSCs versus culture-activated HSCs have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%